Uso de taninos na mitigação da eutrofização e no tratamento de água de reservatórios do semiárido - Medeiros, Guilherme Adler Aciole (2024)
The coagulation process involves the destabilization of colloidal particles (including microorganisms) and suspended matter in water, for subsequent removal in separation units, through the addition of coagulants. Coagulation is one of the tools used in the mitigation of eutrophication, capable of removing algal biomass from water bodies. Additionally, coagulation plays a fundamental role in water treatment for supply, being an essential step in removing suspended particles and impurities, thus ensuring the quality and safety of the drinking water provided to the population. Therefore, this dissertation aimed to evaluate the use of organic coagulants of plant origin in the mitigation of eutrophication and the treatment of water from eutrophicated sources in the Brazilian semiarid region. The first chapter focused on eutrophication mitigation, evaluating the use of three organic plant-based coagulants in the Floc & Sink technique, which involves the coagulation and sedimentation of algal biomass and has been used as a means to mitigate the effects of eutrophication. The three tested coagulants are composed of extracted tannins, chemically modified through the cationization process, from the bark of three different trees: cashew (Anacardium occidentale), black jurema (Mimosa tenuiflora), and Tanfloc SG, obtained from black wattle (Acacia mearnsii). Three different doses of each coagulant (50, 100, and 200 mg.L-1 ) were applied to water samples from four reservoirs in the tropical semiarid region. The results showed that all treatments were capable of removing algal biomass and turbidity, except for the 50mg/L dose of cashew. Increased doses of coagulants resulted in greater removal of biomass and turbidity. Tannin-based coagulants were able to approach the zeta potential to the isoelectric point (0 mV), favoring the neutralization of surface charges of suspended particles. Additionally, no significant changes in water pH were observed after the application of coagulants. Thus, plant-based coagulants emerge as promising alternatives to inorganic coagulants in the Floc & Sink technique, aiming to mitigate the effects of eutrophication in the semiarid region. They represent a potentially more sustainable solution for removing algal biomass in future large-scale applications. The second chapter aimed to evaluate the use of natural tannins as an alternative to metallic coagulants in the treatment of water from eutrophicated reservoirs in the semiarid region for supply. In this chapter, jar test assays were performed with water samples from two semiarid reservoirs. The assays were conducted with 3 tannin-based coagulants: from cashew (Anacardium occidentale), black jurema (Mimosa tenuiflora), and Tanfloc SG, obtained from black wattle (Acacia mearnsii). Four doses (10, 25, 50, and 100 mg.L-1 ) of each coagulant were used. All analyzed coagulants demonstrated a reduction in both turbidity and chlorophyll-a. As the doses of coagulants increased, greater removal of algal biomass and turbidity was observed. The approximation of the zeta potential to the isoelectric point (0 mV) favored the tannins' ability to neutralize the surface charges of suspended particles. Overall, tannins did not cause significant changes in water pH. Although tannin-based coagulants removed algal biomass and turbidity from water, they failed to remove color satisfactorily, making them less promising alternatives for the treatment of water from the studied reservoirs. Our study demonstrated that the tested tannin-based coagulants are potential products for the mitigation of eutrophication in semiarid reservoirs due to their high capacity for removing algal biomass and turbidity. However, their use in water treatment plants for supply is compromised due to their low capacity for color removal.